Influence of the Initial Neutrophils to Lymphocytes and Platelets Ratio on the Incidence and Severity of Sepsis-Associated Acute Kidney Injury: A Double Robust Estimation Based on a Large Public Database - Xiao, Wenyan; Lu, Zongqing; Liu, Yu; Hua, Tianfeng; Zhang, Jin; Hu, Juanjuan; Li, Hui; Xu, Yaohua; Yang, Min (Frontiers in Immunology, 2022)
Background Despite the neutrophil to lymphocyte and platelet (N/LP) ratio has been confirmed as an inflammation-related marker connected with renal dysfunction, its effect on the development of acute kidney injury (AKI) in sepsis patients remained unclear. This study aimed to determine whether the elevated N/LP ratio was associated with the occurrence of sepsis-associated AKI (S-AKI) and severe AKI. Methods Adult septic patients from the MIMIC-IV database were screened and classified into three groups (low, middle, or high) based on their N/LP ratio quartiles. Cox proportional hazard and competing risk models were used to determine the risk of S-AKI in various N/LP groups, whilst logistic regression model and restricted cubic splines (RCS) analysis were employed to investigate the link between N/LP ratios and severe AKI occurrence. Finally, we did doubly robust estimation, subgroup and sensitivity analysis to determine the findings' robustness. Results We categorized 485, 968, and 485 septic patients into low, middle, and high groups. The hazard rate (95% CI) for those in the middle and high N/LP groups on the incidence of S-AKI were 1.30(1.07, 1.58) and 1.27(1.02, 1.59), respectively, as compared to those in the low N/LP group. And the Fine-Gray proportional subdistribution hazards model indicated that death was not a substantial competing risk for S-AKI. Multivariate logistic regression revealed that the risk of severe AKI increased 1.83 fold in high group compared to the low group. The RCS result also suggested that the probability of severe AKI rose significantly when N/LP > 9.5. The consistency of these findings was confirmed using doubly robust estimation. However, subgroup and sensitivity analyses revealed that the association between N/LP and the incidence of S-AKI, severe AKI varied considerably between different populations and diagnostic criteria. Conclusion A raised initial N/LP ratio may induce the development of S-AKI and severe AKI within 7 days after ICU admission in septic patients. These influences were enhanced in older, male, and those with poor health condition. Furthermore, high NLP was more strongly connected to the risk of S-AKI and severe AKI in sepsis patients on the urine output-based AKI criteria than on the serum creatinine-based criteria.